In situ boost and reversible modulation of dual-mode photoluminescence under an electric field in a tape-casting-based Er-doped K0.5Na0.5NbO3 laminar ceramic. Issue 26 (28th May 2019) - Lin, Jinfeng; Lu, Qiling; Wu, Xiao; Sun, Hailing; Lin, Cong; Lin, Tengfei; Xue, Kan-Hao; Miao, Xiangshui; Sa, Baisheng; Sun, Zhimei
Abstract : Er-doping in KNN brings local inhomogenous chemical bonding environment and in situ electric field-induced reversible modulations of dual-mode PL. Abstract : Herein, the tape-casting technique was used to fabricate an Er-doped (K0.5 Na0.5 )NbO3 (KNN:0.02Er) laminar ceramic, which possesses a pseudo-cubic phase structure with regular cube-shaped grains. Considering the substitution behavior of the Er dopant in the KNN lattice, X-ray diffraction analysis and density functional theory simulations both verify that Er can replace K and Na sites. And Er-induced enlargement of the energy band gap of KNN:0.02Er has been obtained in the reflectance spectra and simulations. Furthermore, the ceramic exhibits dual-mode down-conversion and up-conversion photoluminescence (PL). As a lead-free luminescent ferroelectric, the PL intensity of KNN:0.02Er can be enhanced by polarization induced by electric poling. And the dual-mode PL can be obviously modulated under an electric field in an in situ, reversible, real-time and dynamical way. Our results offer an effective theoretical way to bridge the relationship between the crystal structure/chemical bonding environment and the performance of the KNN system, and also provide an opportunity to realize electrically controlled tuning of the PL response in KNN-based luminescent ferroelectrics and the corresponding optoelectronic devices.